2017
DOI: 10.1159/000477244
|View full text |Cite
|
Sign up to set email alerts
|

Hope for CKD-MBD Patients: New Diagnostic Approaches for Better Treatment of CKD-MBD

Abstract: Background: Chronic kidney disease-mineral and bone disorder (CKD-MBD) patients have a huge morbidity and mortality. Only relatively minor progress in therapeutic strategies has been made in the past decades. This is at least partially due to a lack of predictive diagnostic tools allowing personalized treatment of CKD-MBD patients. Summary: In this review we describe recent progress in the diagnosis of disturbances of calcium and phosphate metabolism in patients with CKD-MBD, measuring biological active nonoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 67 publications
(43 reference statements)
1
10
0
Order By: Relevance
“…T50, although strongly influenced by fetuin-A concentrations [1,3], is additionally a dynamic functional serum measure, more broadly affected by other determinantsserum phosphorus, magnesium, and bicarbonate [1,3,36], which are modifiable in CKD [37][38][39]. Thus CKD patients, including KTRs, with shorter duration T50, could be targeted for interventions already familiar to clinicians, which may improve (i.e., prolong) this index of serum calcification propensity [1,3,36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…T50, although strongly influenced by fetuin-A concentrations [1,3], is additionally a dynamic functional serum measure, more broadly affected by other determinantsserum phosphorus, magnesium, and bicarbonate [1,3,36], which are modifiable in CKD [37][38][39]. Thus CKD patients, including KTRs, with shorter duration T50, could be targeted for interventions already familiar to clinicians, which may improve (i.e., prolong) this index of serum calcification propensity [1,3,36].…”
Section: Resultsmentioning
confidence: 99%
“…Thus CKD patients, including KTRs, with shorter duration T50, could be targeted for interventions already familiar to clinicians, which may improve (i.e., prolong) this index of serum calcification propensity [1,3,36]. Phosphoruslowering treatments [37], and magnesium [38] or alkali [39] supplementation are examples of such individual therapies whose experimental capacity to prolong T50 might be considerably enhanced if administered in combination [1,3,36].…”
Section: Resultsmentioning
confidence: 99%
“…Both negative as well as positive calcium balance pose possible health threats in CKD-MBD: negative balance might raise risk of osteoporosis as well as fracture, and positive balance might raise risk for extra-skeletal calcification and cardiovascular events. 16 There is substantial relationship between factors which influence calcium and phosphate regulation. These influences are more complicated in patients having impaired renal function.…”
Section: Introductionmentioning
confidence: 99%
“…Studies performed by leading research groups worldwide done about two decades ago clearly indicated that oxidized PTH (oxPTH) and non-oxidized PTH (n-oxPTH) have completely different biological properties (see reviews [19,20]). All these studies -over 20 in independent groups worldwide -indicate that PTH oxidation is critical for the biological activity of PTH.…”
mentioning
confidence: 99%
“…Huge clinical studies like the EVOLVE trail [13] used iPTH measurements as key inclusion criteria to identify patients with secondary hyperparathyroidism. Intact PTH (iPTH) measurements in these patients, however, do more describe oxidative stress rather than biological active PTH (iPTH correlates much better with biologically non-active oxidized PTH [oxPTH] than n-oxPTH, see references [19,20]). Thus including patients on the basis of iPTH is a poor clinical tool to select patients with secondary hyperparathyroidism.…”
mentioning
confidence: 99%